A method to control bit rate while compressing predicted frames - Barannik, V.; Musienko, A.; Othman Shadi, O. Y.; Kharchenko, N. (IEEE, 2015)
A method to control bit rate while compressing video data subject to approaching maximal quality of the image has been proposed. We use the bisection method to find optimal parameters of the compressor. This method allows us to control the accuracy of the optimal values to find without doing the exhaustive search. Such an approach reduces the frame processing time for a video group.
Keywords: Bit rate; bit rate control; quality level; quantization; luminance component